Student perceptions on enhancing the delivery of physical activity programs in a semi-rural university - Radebe, Silindokuhle Sanele; Breukelman, Gerrit Jan; Joubert, Anné Suzanne; Millard, Lourens (Frontiers in Sports and Active Living, 2025)
Adequate facilities and effective delivery of physical activity programs are essential for promoting active lifestyles among university students, especially in semi-rural contexts where structural barriers can hinder participation. This study investigated student perceptions and recommendations for enhancing the delivery of physical activity programs at the University of Zululand, a semi-rural South African institution. Using a mixed-methods design, quantitative data were collected from 328 full-time students via semi-structured questionnaires, while qualitative insights were drawn from 23 semi-structured interviews with purposively selected participants. Quantitative findings indicated moderate satisfaction with the marking and maintenance of sports facilities (M = 3.20, SD = 1.21, p = 0.004), but neutral perceptions regarding changing room conditions (M = 2.98, SD = 1.29, p = 0.787) and lighting (M = 2.76, SD = 1.24, p = 0.001). Perceptions of communication from the university's Sport and Recreation Services regarding plans and budgets were also low (M = 2.88, SD = 1.02, p = 0.036). Qualitative data supported these results, highlighting limited awareness of available programs, insufficient staff support, and a shortage of qualified coaches. Participants consistently recommended improved infrastructure, enhanced promotional strategies, greater recognition of student-athletes, and increased transparency in communication. These findings underscore the need for targeted institutional reforms to enhance visibility, accessibility, and support within university sport and recreation programs. The study offers practical guidance for institutional policy reform to strengthen the delivery of physical activity programs in semi-rural, under-resourced higher education institutions, ultimately fostering a more active, engaged, and healthier student population.